Cover Image. Issue 4 (28th March 2023) - Higashitani, Atsushi; Teranishi, Mika; Nakagawa, Yui; Itoh, Yukou; Sudevan, Surabhi; Szewczyk, Nathaniel J.; Kubota, Yukihiko; Abe, Takaaki; Kobayashi, Takeshi
Abstract : The cover image is based on the Research Article Increased mitochondrial Ca 2+ contributes to health decline with age and Duchene muscular dystrophy in C. elegans by Atsushi Higashitani et al ., https://doi.org/10.1096/fj.202201489RR .